Effect of botanicals, organic nutrient sources, and bio-control agents on root-knot nematode (Meloidogyne incognita) infecting tomato - Vimala G.; Mansi Machal; Virendra Singh Rana; Abhishek Gowda AP; Vijay Kumar; Najam Akhtar Shakil; Rashid Pervez; Ashish Kumar Singh; Ravinder Kumar; Mukesh Jaiman; Pankaj (Frontiers in Plant Science)
Root-knot nematode (Meloidogyne incognita) causes up to 30% yield loss in tomato (Solanum lycopersicum) worldwide, and reliance on synthetic nematicides poses serious environmental and health risks. This study explores sustainable alternatives by evaluating the nematicidal potential of Mentha spicata and Piper longum essential oils and extracts, along with Bacillus amyloliquefaciens and B. subtilis, under both In vitro and microplot conditions. Essential oils exhibited significant juvenile mortality and egg hatching inhibition at low concentrations, outperforming solvent extracts. In microplots, all treatments—including combinations with organic amendments (farm yard manure, vermicompost, and paddy straw)—significantly reduced nematode populations, improved tomato growth, and enhanced soil fertility. The combined biocontrol treatments performed comparably to the chemical nematicide Velum Prime 400 SC, while also increasing soil organic carbon and NPK content (P < 0.05). These findings demonstrate that integrating botanicals, plant growth promoting rhizobacteria and organic amendments provides an effective, eco-friendly alternative for managing root-knot nematodes, contributing to resilient and sustainable tomato production systems.